Darboux–Protter Spectral Problems for One Class of Multidimensional Hyperbolic Equations - Aldashev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
For a multidimensional hyperbolic equation with a wave operator in the principal part, we show that the Darboux–Protter spectral problem has the countable set of eigenfunctions, and its dual problem is the Volterra problem.